Geoheritage, Geotourism and the Cultural Landscape: Enhancing the Visitor Experience and Promoting Geoconservation - John E. Gordon (Geosciences, 2018)
Geotourism spans a range of visitor interests, from the specialist geotourist to the more general visitor. As well as supporting geoconservation outcomes, it provides economic, cultural, relational and social benefits for both visitors and host communities. The interconnections between geoheritage and the cultural components of the landscape have antecedents in concepts of landscape aesthetics in different cultures. These interconnections provide a range of opportunities for enhancing the geotourist experience and promoting geoconservation and geoeducation by means of activities that involve aesthetic and emotional experiences and interpretation through different cultural filters that encourage the rediscovery of a sense of wonder both about the geological stories in the landscape and the human interactions. A cultural ecosystem services framework provides a holistic approach for informing conservation policy, management and planning for geotourism, enabling assessment of multiple benefits and trade-offs for visitors and communities based on the values of the geoheritage assets. Geotourism studies could also benefit from integration of existing theory, conceptual analysis and practice from broader heritage and nature-based tourism and closer collaboration with relevant social sciences. Adhering to sound geoethical practice is an essential part of geotourism, which can also play a role in the promotion of geoethics among the public and professionals.